A space filled with moving - Anderson, Maggie (Pitt poetry series., 1992)
Previous Praise for Maggie Anderson's Cold Comfort ""We are struck by the generosity of a voice that manages to bridge the gap between a personal and a world view, a balance that reveals a narrator who is of the world yet not overwhelmed by it.""--Prairie Schooner